Sosialisasi “Calling and Career” melalui program Career Day di kalangan murid SMAK IPEKA Balikpapan - Alfian Samudra Alfian (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Humans are created by God with a primary purpose to enjoy and glorify Him. When we refer to this purpose, all human existence should be directed towards Him, including their work. One form of glorifying God in work is by doing something that is in accordance with His calling, which is in line with the design that He has prepared. One such platform is the Career Day Program to show every student of SMAK IPEKA Balikpapan to be able to recognize the calling that has been given to them through self-knowledge and help them to know what the world needs nowadays. It also helps them to see various careers as their reference for their future life. Keywords: Career Day Program, Job, Call, Self-knowledge